Pengaruh Angka Perceraian di Pulau Jawa Akibat Kasus Kekerasan dalam Rumah Tangga - Darmawan Darmawan (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Java Island has the most dense population in Indonesia. This is in line with the number of marriages and divorces that occur. One of the factors causing divorce is violence that occurs in the household. Violence is a physical act that often occurs in the scope of life. Based on the data obtained, there are 14 factors for divorce in Indonesia. factors include adultery, drunkenness, madness, gambling, death of one of the parties, imprisonment, polygamy, domestic violence, physical disability, continuous disputes and quarrels, forced marriage, apostasy, economics, and so on. On the island of Java, there are 4 factors that cause the highest number of divorces, namely disputes and quarrels, the economy, the death of a spouse and domestic violence. Handling and efforts to prevent domestic violence cases need to be the attention of parties who have the authority to resolve them and no longer become a serious problem in the household and surrounding environment.